Minimally Invasive versus Conventional Mitral Valve Surgery: Procedures and Early Outcomes - Ahmed Emara (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Minimal invasive mitral valve surgery gained wide acceptance. However, criticism continuous about its ability to replace the conventional full sternotomy technique.Aim of the work: The study aimed to compare between the full sternotomy and less invasive approaches for mitral valve surgery.Patients and Methods: The study recruited 100 patients. They were allocated to one of two equal groups [the traditional and minimal invasive approach]. All patients were thoroughly evaluated by history taking, physical examination, laboratory and ancillary radiological investigations. Assessment included incision length, weaning events, aortic cross clamp time, total bypass and operative times, rate of conversion from minimally invasive technique to full sternotomy. In surgical intensive care unit, ventilation hours, post-operative pain and need for analgesia, re-exploration for bleeding, blood loss and blood transfusion, and any complications were documented.Results: Preoperative New York Heart Association [NYHA] class was significantly different between groups A and B. But, no significant difference was reported for patient demographic or preoperative data. The incision length and cross clamp time was shorter in A than B group [6.56±1.88 cm, 61.78±35.91 minutes’ vs 12.54±1.78 cm, and 78.08±36.24 minutes, respectively]. Otherwise, the cannulation, bypass, operative times were significantly longer among group A. The ventilation, ICU stay, hospital stay, bleeding, serum creatinine and pain scores were significantly lower among group A. the postoperative events were comparable between both groups with slight increase of neurological events in A group [3 cases] than B group [2 cases]. At 6 months, both groups yielded non-significant difference, regardless of better outcome at direct postoperative time.Conclusion: Minimal invasive mitral valve surgery had a good short and mid-term outcome as the conventional sternotomy approach. It could replace the conventional approach as a gold-standard for mitral valve surgery.